(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Epithelial ovarian cancer is a major cause of gynecological cancer-related mortality because most patients are diagnosed at an advanced stage. Early detection remains difficult due to nonspecific symptoms and absence of an ideal screening test. Cancer antigen 125 (CA-125) is widely used but has limited specificity in benign gynecological disorders and reduced sensitivity in early-stage disease. Human epididymis protein 4 (HE4) and the Risk of Ovarian Malignancy Algorithm (ROMA), which combines HE4, CA-125 and menopausal status, have been proposed to improve diagnostic accuracy. Objective: To systematically evaluate the diagnostic performance of HE4, CA-125 and ROMA score in early detection of epithelial ovarian cancer. Methods: A systematic review was conducted according to PRISMA 2020 principles. PubMed, Scopus, Web of Science, Embase and Google Scholar were searched for studies evaluating HE4, CA-125 and/or ROMA score in women with suspected ovarian malignancy or adnexal masses. Studies reporting sensitivity, specificity, positive predictive value, negative predictive value or area under the curve were included. Histopathological diagnosis was considered the reference standard. Study quality was assessed using QUADAS-2. Owing to methodological and clinical heterogeneity, findings were synthesized narratively with pooled descriptive estimates. Results: A total of 684 records were identified. After removing 156 duplicates, 528 records were screened. Eighty-one full-text articles were assessed, and 31 studies involving 8,972 women were included. Of these, 2,744 women had epithelial ovarian cancer and 6,228 had benign ovarian or gynecological conditions. Early-stage disease was reported in 1,126 epithelial ovarian cancer cases. Overall, CA-125 showed pooled sensitivity of 80.8% and specificity of 75.4%. HE4 showed sensitivity of 76.9% and higher specificity of 89.6%. ROMA score demonstrated the best overall diagnostic balance, with sensitivity of 86.3%, specificity of 84.8% and AUC of 0.92. In early-stage epithelial ovarian cancer, ROMA showed sensitivity of 74.9%, followed by HE4 at 69.5% and CA-125 at 63.7%. Conclusion: HE4 and ROMA score improve diagnostic specificity and risk stratification compared with CA-125 alone. ROMA score provides the best overall diagnostic performance, particularly when menopausal status is considered. However, none of these biomarkers is sufficiently accurate as a standalone screening test for early epithelial ovarian cancer. Their greatest clinical value lies in combination with imaging, clinical assessment and histopathological confirmation.